EFEKTIVITAS KEMITRAAN DENGAN METODE EKSPERIMEN PADA PENGOLAH IKAN KERING DI KABUPATEN REMBANG - Anik Nurhidayati; Maslichan Maslichan (BBM (Buletin Bisnis & Manajemen), 2015)
This study aims to support the development of SMEs fish processing. The formulation ofthe issues raised are SMEs dried fish processors in determining the choice of formpartnerships that benefit both parties, is able to distinguish the effectiveness ofpartnerships that were given a loan and that without being given a loan in advance. Thehypothesis in this study suspected effectiveness of partnerships with first capital loanedable meningkatkkan performance so that the fish processing SME development in thecoastal environment Rembang be increased. After testing the instrument with the resultsof all valid and reliable research instrument. From the results of the Kolmogorov-Smirnovtest statistic and is based on the real level of 0,05 can be concluded that the data ofSMEs in partnership with capitalized first is normal. Data normality test results SMEswith capitalized first Kolmogorov-Smirnov statistic is 0,070 and alpha of 0,05 means thatH0 is accepted. Medium Data SMEs without prior dimodali Kolmogorov-Smirnov statisticof 0,082 and 0,200 significance alpha of 0,05 means that H0 is accepted. The results ofthe t test for SMEs which is capitalized in advance and that without statistical valuesobtained capital t = 2,944 and 0,004 significance value < 0,05. Because the significancevalue is smaller than the real level, we conclude H0 is rejected or no significancedifference in SMEs which are given in advance and the capital without capitalized toincrease performance so that the development of SMEs dried fish processors canincrease sales and economic growth.Keyword: partnership, business development